Measurement of Pen Pressure of Offline Signatures Using 3D Digital Microscopy and Its Utility in Determining Authorship - Kaya, Dilara Öner; Çetin, Gürsel (The Bulletin of Legal Medicine, 2024)
Objective: Two of the most frequently used diagnostic criteria in writing and signature comparisons are the degree of pen pressure and variations in pen pressure. However, in today’s practice, this criterion is inferentially evaluated only by naked eye or using image enhancer tools. This situation may cause various results among examiners, and difficulties in judicial procedure in terms of forensic handwriting and signature examinations, which has already been criticized for subjectivity. In this study, it is aimed to measure the depth of the indented pen pressure numerically in offline signatures and to evaluate it more objectively compared to the classical methods.Methods: Note that 10 male and 10 female subjects participated in this study. Subjects were asked to imitate the signature shown as an example on three different surfaces. This signature was imitated by the subjects three times on different surfaces via free-hand (practise and non practice). Depth measurements were taken from five different points on the signature using a Leica DVM-6 3D Digital Microscope and compared with the genuine signature.Results: Statistically significant differences were reported at different confidence intervals in comparisons considering different combinations.Conclusion: In conclusion, aside from similar depth of the indented pen pressure, persistence of dissimilarities in different comparison documents and at different points is an important criterion. It has been revealed that these differences are statistically significant.
Keywords: 3D Digital Microscope; Genuine signature; Simulation; Pen pressure; None practiced free-hand; Practiced free-hand